EFEKTIVITAS PROGRAM 7K DI MIN 3 ACEH BARAT - Dian Ayuningtyas; Bakhtiar; Nindi Destari (Program Studi Manajemen Pendidikan Islam, 2023)
This research discusses a school program, namely the 7K program (piety, cleanliness, health, drunkenness, neatness, beauty, shadyness). This study used a qualitative approach with data collection techniques using interviews, observation, and documentation. Respondents in this study were school principals, teachers, and students. The results showed that the factors causing the ineffectiveness of the 7K program at MIN 3 West Aceh were school facilities and infrastructure, student self-awareness, and motivation from teachers to students. Facilities and infrastructure factors can also be used as a support for the running of the 7K program because each program will run if all the necessary facilities and infrastructure are available. The self-awareness factor aims to create students, teachers and the school community to know and understand about maintaining beauty so that the desire to maintain the beauty of the school is created. Motivating factors for students can create students who want to comply with school rules and also want to carry out activities in school. With the motivation of teachers and parents of students, students have a sense of responsibility to look after their school and comply with existing regulations.